2002
DOI: 10.1097/00004647-200204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of VEGF and Angiopoietin Expression with Disruption of Blood–Brain Barrier and Angiogenesis after Focal Cerebral Ischemia

Abstract: In an effort to elucidate the molecular mechanisms underlying cerebral vascular alteration after stroke, the authors measured the spatial and temporal profiles of blood-brain barrier (BBB) leakage, angiogenesis, vascular endothelial growth factor (VEGF), associated receptors, and angiopoietins and receptors after embolic stroke in the rat. Two to four hours after onset of ischemia, VEGF mRNA increased, whereas angiopoietin 1 (Ang 1) mRNA decreased. Three-dimensional immunofluorescent analysis revealed spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
285
2
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(315 citation statements)
references
References 57 publications
21
285
2
7
Order By: Relevance
“…The present study confirms observations of microvessel hyperdensities in the ischemic infarction zone (Manoonkitiwongsa et al, 2001a) and is consistent with previous studies that indicate that angiogenesis induced by ischemia is not a widespread reaction of parenchymal microvessels in the entire ischemic zone distal to MCA occlusion (Marti et al, 2000;Zhang et al, 2000Zhang et al, , 2002. This is reminiscent of the localized angiogenesis observed after myocardial infarct where it has been postulated that a spatially restricted pattern of thrombospondin-1 in the infarct margin limits the spread of both ischemic inflammation and angiogenesis (Frangogiannis et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The present study confirms observations of microvessel hyperdensities in the ischemic infarction zone (Manoonkitiwongsa et al, 2001a) and is consistent with previous studies that indicate that angiogenesis induced by ischemia is not a widespread reaction of parenchymal microvessels in the entire ischemic zone distal to MCA occlusion (Marti et al, 2000;Zhang et al, 2000Zhang et al, , 2002. This is reminiscent of the localized angiogenesis observed after myocardial infarct where it has been postulated that a spatially restricted pattern of thrombospondin-1 in the infarct margin limits the spread of both ischemic inflammation and angiogenesis (Frangogiannis et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Gliomas express a range of growth factors and cytokines, however VEGF is unique among these growth factors in that it induces VP as well as neovascularization [55][56][57][58]. Intra-cranial administration of recombinant VEGF to mice has been shown to increase VP and result in breakdown of the BBB, however the mechanisms regulating this process remain poorly understood [59][60][61]. Therefore, in this study we have examined Src-deficient mice, which we have previously shown to have a 'leakage-resistant' phenotype in response to VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent stroke, alteration of angiopoietin-1 in the ischemic core mediates BBB disruption whereas angiopoietin-2 regulates neovascularization. 114 In stroke patients, increased blood levels of angiopoietin-1 are associated with tPA-related hemorrhage. 115 High-mobility-group-box-1 is also involved in neurovascular repair after ischemic stroke.…”
Section: Delayed Hemorrhagic Transformationmentioning
confidence: 99%